PETUNJUK RASULULLAH SAW TENTANG HAK PESERTA DIDIK - Abdul Wahab Syakhrani; Nur Azizah, Riska Aulia Rahmah, Sri Norhafizah (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2022)
Learners are the target (object) and at the same time as the subject of education. In the view of Islamic education, to know the nature of students, cannot be separated from the discussion of human nature, because humans are the result of an educational process. In essence, the concept of Islamic teachings, are God's creatures that are biologically created through a process of growth and development that takes place in an evolutionary manner, that is, through a gradual process. All students have the right to get proper facilities and the same educational services as other students. So in education, educators must be fair to their students, because by being fair can make the learning that is taught run effectively. It's the same thing as a teacher in giving lessons to his students is expected to be gentle and affectionate, so that they avoid harmful behavior in the learning process